Separation of organophosphorus pesticides using micellar electrokinetic chromatography - Monjurul Alam, S. M. (2005)
This study was undertaken to separate hydrophobic and hydrophilic organophosphorus pesticides (OPPs) using micellar electrokinetic chromatography (MEKC) with on-column UV detection and the challenge of decreasing the limit of detections (LODs) was tried to meet by online concentration methods. The influence of separation buffer and sample matrices were investigated with respect to migration, efficiencies, peak shapes and resolution. Successful separation of hydrophobic OPPs (methidathion, diazinon, quinalphos, chlorpyrifos and profenofos) was achieved by normal mode MEKC with sodium dodecyl sulphate, SDS (NM-MEKC-SDS) that comprised a separation buffer of 10 mM phosphate-borate (pH 9.3), 10 mM SDS and 10 % v/v 1:1 mixture of methanol-acetonitrile, where sample was prepared in similar buffer matrix and injected electrokinetically. An alternative approach is proposed to predict the retention factors (k), on the basis of a functional relationship between solutes retention and separation potentials. Using online concentration technique (sweeping-NM-MEKC-SDS), sensitivity enhancement factors (SEFarea and SEFheight) were found to be 10 for each pesticide. Sensitivity enhancement was improved further for diazinon, quinalphos and profenofos (LODs in sub-ppm range) by increasing the sample plug length. Hydrophilic OPPs (phosphamidon, dicrotophos and monocrotophos) were successfully separated in both basic and acidic phosphate buffer. At least 100-fold improvement in detector response was achieved by stacking in reverse migrating micelles (SRMM) that corroborated the LODs in sub-ppm level, and those levels were found detectable by spiking in a natural water sample. The methods developed here, sweeping-NM-MEKC-SDS for hydrophobic OPPs and SRMM for hydrophilic OPPs are expected to be useful either by direct injecting the sample upon filtration or with prior suitable offline sample enrichment steps depending on the contaminant level.